How often do parents administer medications to their children in hospital? A prospective direct observational study - Johanna I Westbrook; Tim Badgery-Parker; Virginia Mumford; Magdalena Z Raban; Alison Merchant; Erin Fitzpatrick (BMJ Open Quality)
Parents and carers play a critical role in supporting their children while in hospital. Multiple qualitative studies have explored parental involvement in the care of hospitalised children. Administration of medication to young children can be difficult and cause anxiety and stress for children. Parents are often willing and able to assist, yet little is known about how often parents are given responsibility for medication administration in hospital.We analysed data from a prospective direct observational study of nurses administering medication at a major paediatric referral hospital in Australia. Data from observations of 298 nurses preparing and administering 5137 medication doses to children on nine medical and surgical wards between 07:00 and 22:00 were analysed. Details of drugs administered, whether medications were left for parents/carers to administer, and if nurses observed the administration by parents, were recorded.Parents were at their child’s bedside during 89.7% (n=4610) of observed medication administrations. Parents gave 20.3% (n=1045) of medications. In 14.3% (n=733), medications were left with parents to administer without a nurse present. In 6.1% (n=312) of doses, medications were given to parents, but the administration was observed by a nurse. Parents were most likely to be given medications to administer to young children (1–5 years), and the medications most frequently administered were analgesics and anti-epileptics.Parents/carers are integrally involved in the administration of many medications to children in hospital. The extent of parents’ role and the impact on medication administration efficiency has been largely absent from the healthcare literature. Given that one in five medication doses is administered by parents, hospitals should recognise this contribution and consider if any additional support for parents is required.